Perlindungan Data Pribadi Konsumen dalam Transaksi E-Commerce: Perspektif Hukum Dagang dan UU Nomor 27 Tahun 2022 Tentang Pelindungan Data Pribadi - Mudawaroh Mudawaroh; Dewa Sukma Kelana; Basyarudin (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
The rapid growth of e-commerce transactions in Indonesia increases the risk of misuse of consumer personal data. This study aims to analyze personal data protection in e-commerce transactions from the perspective of commercial law and Law Number 27 of 2022 concerning Personal Data Protection (PDP Law), and to identify challenges in its implementation. The study uses a normative juridical method with a statutory regulatory, conceptual, and comparative study approach. Data were obtained through a documentary study of laws and regulations, scientific literature, journals, and related legal documents. Data analysis was conducted qualitatively through legal inventory, data classification, legal interpretation, and drawing conclusions. The results show that before the enactment of the PDP Law, personal data protection regulations in Indonesia were still sectoral and scattered across various regulations, thus not providing adequate legal certainty. The PDP Law strengthens personal data protection by regulating data subject rights, data controller obligations, data processing mechanisms, and administrative and criminal sanctions for violations. However, the implementation of the PDP Law still faces challenges in the form of harmonization of sectoral regulations, compliance monitoring, and regulation of cross-border data transfers. These findings indicate that the effectiveness of personal data protection in the e-commerce ecosystem is not only determined by the existence of regulations, but also by institutional readiness and oversight mechanisms.